Syariat Penyembelihan dan Pendistribusian Daging Kurban dalam Tafsir Fiqih Imam Syafi’i: Studi Kasus di Indonesia - Febry Rudiantara; Haiyin Lana Lazulfa; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the shari'a of slaughtering and distributing sacrificial meat in the interpretation of Imam Shafi'i. This study uses a qualitative approach by applying descriptive-analytical methods through literature studies and field studies. The formal object of this research is the interpretation of Imam al-Shafi'i fiqh. While the object of this research is the slaughter and distribution of sacrificial meat. The context of this research is mosques in several locations in West Java, Indonesia. The results of the research and discussion show that the law of sacrificial worship is understood by the sunnah mu'akkad following the Shafi'i school which takes the interpretation of bi al-matsur in the interpretation of the Koran by carrying out the slaughter and distribution of various sacrificial meats based on the implementation in 1442 H in three locations. The conclusion of this study is that the implementation of qurbani shows practices that are in accordance with the rules of Imam Syafi'i law, although there are also practices outside the rules, such as the sale of the skin and bones of the sacrificial animal in one location, where this is a consequence of the dynamics of sharia in Indonesia.